The Role of Psychological Capital and Readiness for Change in Rural Tourism: A Phenomenological Study - Hana Angriyani Mardika; Bambang Suharto; Dimas Novian Syahputra (Universitas Ahmad Dahlan, 2024)
Many villages aspire to boost their tourism industry, but numerous ones face challenges due to limited ownership of three key elements: economic assets, intellectual capital, and social capital. However, a more critical factor contributing to the development of rural tourism is Psychological Capital (PsyCap). This research aims to assess the implementation of PsyCap and the readiness for change among small and medium-sized enterprise (SME) actors, serving as the primary driving force behind rural tourism. The study employs a qualitative approach, utilizing data collection techniques such as documentary studies, observation, focus group discussions (FGDs), and interviews. The participants include five MSME actors and three coordinators of the Tourism Awareness Association (Pokdarwis) in Durensari village, Trenggalek. The data were analyzed using NVivo 12. The findings reveal that human resources, including local tourism associations and a strong sense of community unity, demonstrate positive psychological capital, contributing to the outstanding success of their tourism village despite starting with very limited financial, intellectual, and social resources. The adaptive attitudes of these participants reflect their readiness for change. Further discussion is explained in the article.